Pengaruh Penggunaan Face Mist Wortel (Daucus Carota L) untuk Perawatan Kulit Wajah Kering - Azizah Zahrah; Mitra Lusiana (Institut Nalanda, 2024)
Dry facial skin is a condition where the skin appears dull, flaky, and shows fine lines or wrinkles, leading to discomfort and a lack of confidence. In this study, the researcher used carrot face mist for the treatment of dry facial skin. The aim of this research is to analyze the effect of using carrot face mist for the treatment of dry facial skin on both the control group and the experimental group, with a usage frequency of twice a day. This research is an experimental study using a quasi-experimental method. The sample consisted of 6 individuals selected through purposive sampling. The type of data used is primary data. Data analysis involved normality tests, homogeneity tests, and T-tests. The results of the study indicate that the control group (X0) without the use of carrot face mist did not show significant changes in the indicators of facial skin moisture. In contrast, the experimental group (X1) using carrot face mist demonstrated significant changes, although the skin did not yet reach a fully moisturized state. The findings confirm a significant difference in the effects of treating dry facial skin using carrot face mist between the control group and the experimental group, with a significance level of 0.011 < 0.050.